Allogeneic hematopoietic stem cell transplantation following reduced‐intensity conditioning for mycosis fungoides and Sezary syndrome. Issue 1 (14th October 2014) - Shiratori, Souichi; Fujimoto, Katsuya; Nishimura, Machiko; Hatanaka, Kanako C.; Kosugi‐Kanaya, Mizuha; Okada, Kohei; Sugita, Junichi; Shigematsu, Akio; Hashimoto, Daigo; Endo, Tomoyuki; Kondo, Takeshi; Abe, Riichiro; et al.
Abstract: Advanced‐stage mycosis fungoides and Sezary syndrome (MF/SS) have a poor prognosis. Allogeneic hematopoietic stem cell transplantation (HSCT), particularly using a reduced‐intensity conditioning (RIC) regimen, is a promising treatment for advanced‐stage MF/SS. We performed RIC‐HSCT in nine patients with advanced MF/SS. With a median follow‐up period of 954 days after HSCT, the estimated 3‐year overall survival was 85.7% (95% confidence interval, 33.4–97.9%) with no non‐relapse mortality. Five patients relapsed after RIC‐HSCT; however, in four patients whose relapse was detected only from the skin, persistent complete response was achieved in one patient, and the disease was manageable in other three patients by the tapering of immunosuppressants and donor lymphocyte infusion, suggesting that graft‐versus‐lymphoma effect and 'down‐staging' effect from advanced stage to early stage by HSCT improve the prognosis of advanced‐stage MF/SS. These results suggest that RIC‐HSCT is an effective treatment for advanced MF/SS. Copyright © 2014 John Wiley & Sons, Ltd.